Circadian rhythms of antioxidant enzymes activity, clock, and inflammation factors are disrupted in the prefrontal cortex of aged rats. Potential targets for therapeutic strategies for a healthy aging. - Ponce, Ivana Tamara (2024)
Age impairs cognitive functions and antioxidant defenses, for example, by increasing oxidative stress and inflammation in the brain. However, to date, there are no reports on the consequences of aging on temporal patterns of lipid and protein oxidation, antioxidant enzymes activity, the endogenous clock, and proinflammatory cytokines in the prefrontal cortex (PFC). Therefore, our objectives were 1) to investigate the endogenous nature of 24-h rhythms of lipid peroxidation, protein carbonyl levels, catalase (CAT) and glutathione peroxidase (GPX) activity as well as retinoic acid-related orphan receptor a (RORa) and tumor necrosis factor alpha (TNF-α) levels, in the rat PFC, and 2) to study the consequences of aging on the circadian organization of these factors in this area. To do that, we used male Holtzman rats, maintained under constant darkness conditions for 15 days before reaching 3- and 22-mo-old, respectively. PFC samples were isolatedevery 4 h under dim-red light for a 24 h period. Our results revealed circadian patterns of antioxidant enzymes activity, oxidative stress, RORa and TNF-α protein levels in the PFC of young rats. The circadian distribution of the rhythms’ acrophases suggests reciprocal communicationamong antioxidant defenses, endogenous clock, and inflammation. Such circadian organization disappears in the PFC of aged rats. Increased oxidative stress modifies the cellular redox environment and, consequently, alters the endogenous clock activity and disrupts the circadianorganization of antioxidant defenses and TNF-α in the PFC. These results might highlight novel chronobiological targets for the design of therapeutic strategies for healthy aging patients.